Novel mode III DCB test setups and related evaluation methods to investigate the fracture behaviour of adhesive joints. (February 2023) - Schrader, Peer; Marzi, Stephan
Highlights: Two mode III test setups are proposed for determining ERR and cohesive traction. SBT and CBT methods using rotational angle of load introduction points are proposed. Backface strain measurements for measuring crack extension and process zone length. J -integral evaluation allows the most accurate determination of critical ERR. Abstract: In this work, two test setups in proximity to the familiar Double Cantilever Beam and Tapered Double Cantilever Beam tests are proposed which allow for determining the critical mode III energy release rate (ERR) of adhesive joints. The experiments are performed on an elastic–plastic adhesive (SikaPower® 498) and evaluated using data reduction schemes based on nonlinear elastic fracture mechanics ( J -integral) and linear elastic fracture mechanics (Irwin-Kies equation). Next to the data reduction schemes based on linear elastic fracture mechanics in accordance with ISO 25217, crack length independent and corrected beam theory approaches are presented which incorporate measurements of the rotational angles of the load introduction points. Crack length and process zone length are measured during the experiments using backface strain measurements. Furthermore, a multi-specimen compliance calibration is employed to allow simplified testing in future studies. The obtained critical ERRs and cohesive laws are compared and discussed thoroughly to gain insight into the advantages and disadvantages of the different data reduction schemes. The results implicate that the J -integral evaluation method is the most reliable for evaluation of the mode III fracture energy, as no assumptions need to be made about the behaviour of the adherends when determining the mode III ERR.